A Clean Sharp Image: Don Cherry’s Suits as Sartorial Statements (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Canadian sports commentator Don Cherry is notorious for his outspoken opinions and flamboyant style, both attracting popular attention. This article examines his attention-grabbing on-air style as an extension of both his values for the game of hockey and his view of himself as a working-class boy made good. I argue that Cherry deliberately uses his suits to embody his social and personal values. Drawing on fashion studies approaches, I show that while not exactly fashionable in terms of trendiness, Cherry’s suits are examples of the ability of clothing to be indexical of working-class personality transformed.